2020
DOI: 10.1016/j.ajur.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Peak stent discomfort occurs early and ureteral stent with distal loop design has less pain–A pilot prospective randomised single-blinded trial over 2 weeks

Abstract: Objectives The Polaris™ loop ureteric stent reduces the severity of stent discomfort by minimising stent material in the bladder. Early impact of ureteral stenting on quality of life (QoL) within 1 week remains unclear. The usefulness of the patient-administered ureteral stent symptoms questionnaire (USSQ) during this period of stent insertion was assessed. In this pilot single-blinded prospective randomised study, we investigate 1) the presence of early (within the 1st week) stent discomfort via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…used a pigtail suture stent instead of the lower part of the double J ureteral stent, and the study demonstrated a clear bene t of the pigtail suture stent in terms of urinary and pain symptom scores, along with dilatation of the ureter without in ammation around the suture [18]. Other studies have shown that the use of shtail stent or pigtail suture stent can signi cantly reduce ureteral stent-related symptoms, but it has shortcomings such as expensive, poor practicality and others [19,20,21,22]. So we have designed a simple and practical ureteral stent tube improvement scheme, which was improved on the basis of the original Bard ureteral stents, further closer to the shape of the tail bracket, avoid the in uence of the material the distal ureter and bladder mucous membrane irritation, hope to be able to alleviate symptoms of patients with ureteral stent, and reduce the economic costs for patients at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…used a pigtail suture stent instead of the lower part of the double J ureteral stent, and the study demonstrated a clear bene t of the pigtail suture stent in terms of urinary and pain symptom scores, along with dilatation of the ureter without in ammation around the suture [18]. Other studies have shown that the use of shtail stent or pigtail suture stent can signi cantly reduce ureteral stent-related symptoms, but it has shortcomings such as expensive, poor practicality and others [19,20,21,22]. So we have designed a simple and practical ureteral stent tube improvement scheme, which was improved on the basis of the original Bard ureteral stents, further closer to the shape of the tail bracket, avoid the in uence of the material the distal ureter and bladder mucous membrane irritation, hope to be able to alleviate symptoms of patients with ureteral stent, and reduce the economic costs for patients at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of distal anchors, "pigtail suture stents" and braided stents that eliminate the distal pigtail, and much or all of the mid-ureteral section of a stent-replacing these elements by a suture or braid-have been proposed (11)(12)(13)(14). A recent patient trial showed promising results in terms of reduction in stent-related symptoms (13).…”
Section: Discussionmentioning
confidence: 99%
“…And yet, notwithstanding the recognition that kidney and bladder anchors may be the major cause of patient discomfort, it should be noted that the fundamental double-J design has remained essentially unchanged. Recent efforts to address this aspect have focused on removing the distal J anchor (11)(12)(13) or otherwise minimizing stent material in the bladder (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Based on various studies, placement of double J ureteric stent is associated with morbidity in the majority of patients ranging from generalized urinary discomfort to urinary tract infection/obstruction. It also adversely affects patients' quality of life (Pietropaolo et al, 2022;Camtosun & Bicer, 2020;Lim et al, 2020). So, this study conducted in an attempt to provide patients with necessary instructions required to minimize the effects of double J ureteric stent.…”
Section: Significance Of the Studymentioning
confidence: 99%